2019
DOI: 10.1016/j.jcss.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Sorting networks: To the end and back again

Abstract: New properties of the front and back ends of sorting networks are studied, illustrating their utility when searching for bounds on optimal networks. Search focuses first on the "outsides" of the network and then on the inner part. Previous works focused on properties of the front end to break symmetries in the search. The new, out-side-in, properties shed understanding on how sorting networks sort, and facilitate the computation of new bounds on optimality. We present new, faster, parallel sorting networks for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 21 publications
(67 reference statements)
1
32
0
Order By: Relevance
“…Optimizing sorting networks for small inputs is an active research area in parallel programming. Knuth [60] and later Codish et al [61] gave networks for sorting up to 17 numbers that were later shown to be optimal in depth, and up to η ≤ 10 also optimal in the number of comparators. Optimizations for up to 20 inputs have recently been achieved, see Table 1 in [61].…”
Section: Resource Analysis Of Quantum Sorting Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimizing sorting networks for small inputs is an active research area in parallel programming. Knuth [60] and later Codish et al [61] gave networks for sorting up to 17 numbers that were later shown to be optimal in depth, and up to η ≤ 10 also optimal in the number of comparators. Optimizations for up to 20 inputs have recently been achieved, see Table 1 in [61].…”
Section: Resource Analysis Of Quantum Sorting Networkmentioning
confidence: 99%
“…Knuth [60] and later Codish et al [61] gave networks for sorting up to 17 numbers that were later shown to be optimal in depth, and up to η ≤ 10 also optimal in the number of comparators. Optimizations for up to 20 inputs have recently been achieved, see Table 1 in [61]. In such optimizations one typically distinguishes between the optimal depth problem and the problem of minimizing the overall number of comparators.…”
Section: Resource Analysis Of Quantum Sorting Networkmentioning
confidence: 99%
“…The previous lemma leads to the following result: The graph in figure 2 has only four perfect matchings: (2,1,3,4,5), (3,1,2,4,5), (2,1,3,5,4), (3,1,2,5,4). So, when testing subsumption, instead of verifying 5!…”
Section: Enumerating Perfect Matchingsmentioning
confidence: 96%
“…The last results for parallel sorting networks are for 17 to 20 inputs and are given in [8], [5]. On the other side, the paper [6] proved the optimality in size for the case n = 9 and n = 10.…”
mentioning
confidence: 95%
“…Domain-specific techniques such as mathematically designing the prefix layers [7,8] or utilizing certain symmetries [40] were not used.…”
Section: Representationmentioning
confidence: 99%